PENINGKATAN KECAKAPAN HIDUP MELALUI PENDIDIKAN KELUARGA BERWAWASAN GENDER (PKBG) - hasim, sarifa suhra (PSW, 2015)
One form of program services Directorate of Public Education is implementing a Gender Perspective Family Education program (PKBG) which is a program attempts to achieve justice and gender equality in the family. The program is based on the fact that as long as there is still a tendency that womens participation in various aspects of development are still relatively low compared with men. The main factors of this condition is still the stereotype (negative labeling) which is based on sex, where women are considered to have the space for a more limited compared with men, especially in communities that are economically poor. This condition is referred to as gender bias. The existence of this program is perceived community program participants can help their lives in various ways as material touches on life skill programs that enable women can increase life skills in a particular field ifferent 5 fields include; Democracy and Human Rights, Gender Equality and Justice, Life Skills / life skills (academic, personal, social, and vocational), Parenting, Seaweed Cultivation.